Os sem terrinha no Movimento dos Trabalhadores Rurais sem Terra (MST) - Da Mata, Liene Keite de Lira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study addressed the following key questions: Who are the Landless Children? Which brings the subject to identify themselves as Landless Children, a representative name of an identity? As the Landless Children are engaged in the social struggle of the Landless Rural Workers Movement (MST)? Thus, the research aimed to verify the political organization of the Landless Children Movement and Specific aims at detecting areas, local and agents involved in the preparation and organization of children in the process of policy formation and participation in the social struggle; investigate, in the media built by the Movement to children and youth, training of evidence and political participation of the Landless Children; check for in the school of influence of the Movement, contribution to the formation and political participation of the Landless Children in the social struggle. The methodological procedures for the research consisted of consulting and document analysis of periodicals and site related to the theme, literature study and the authors of texts devoted to children in the MST and political training of Landless Children; empirical research in the City Peasant School Chico Mendes in Querencia North-Paraná, Movement camp school, where there were observations and consultation to school Pedagogical Policy Project; written statements of children who participated in the Meeting of the Landless Children; semi-structured interviews with educators, coordination and direction. We conclude that the Landless Children identify themselves and are identified by name from the meetings of mobilizations of Landless Children, created by the Movement for children and adolescents to express themselves in the struggle for agrarian reform and social rights as school and education. Thus the name Landless Children identifies a subject itself and represents a sense of belonging and political formation that may relate differently in each child and...

A presente pesquisa levantou as seguintes questões chaves: Quem são os Sem Terrinha? O que leva os sujeitos a identificarem-se como Sem Terrinha, um nome próprio representativo de uma identidade? Como os Sem Terrinha são engajados na luta social do Movimento dos Trabalhadores Rurais Sem Terra (MST)? Assim, a pesquisa teve como objetivo geral verificar a organização política dos Sem Terrinha no Movimento e, como objetivos específicos detectar os espaços, locais e agentes envolvidos na preparação e organização das crianças no processo de formação política e participação na luta social; investigar, nos meios de comunicação construídos pelo Movimento ao público infanto-juvenil, indícios de formação e participação política dos Sem Terrinha; verificar se há, na escola de influência do Movimento, contribuição na formação e participação política dos Sem Terrinha na luta social. Os procedimentos metodológicos para a realização da pesquisa constaram de consulta e análise documental de periódicos e sitio relacionados à temática, pesquisa bibliográfica e estudo dos textos de autores dedicados à infância no MST e à formação política dos Sem Terrinha; pesquisa empírica na Escola Camponesa Municipal Chico Mendes em Querência do Norte- Paraná, escola de acampamento do Movimento, onde ocorreram observações e consulta ao Projeto Político Pedagógico da escola; depoimentos escritos de crianças que participaram do Encontro dos Sem Terrinha; entrevistas semiestruturadas com educadores, coordenação e direção. Concluímos que os Sem Terrinha se identificam e são identificados pelo nome próprio a partir das mobilizações de Encontros dos Sem Terrinha, criados pelo Movimento para crianças e adolescentes manifestarem-se na luta pela Reforma Agrária e direitos sociais como escola e educação. Assim, o nome Sem Terrinha identifica um sujeito próprio e representa um sentimento de pertença e formação...
Keywords: Educação; Reforma agraria; Conflito social; Educação de crianças; Education